Natural Fiber-Reinforced Polylactic Acid, Polylactic Acid Blends and Their Composites for Advanced Applications - Ilyas R.A.; Zuhri M.Y.M.; Aisyah H.A.; Asyraf M.R.M.; Hassan S.A.; Zainudin E.S.; Sapuan S.M.; Sharma S.; Bangar S.P.; Jumaidin R.; Nawab Y.; Faudzi A.A.M.; et al. (MDPI, 2023)
Biodegradable polymers; Fiber reinforced plastics; Hybrid composites; Lactic acid; Natural fibers; Polymer matrix composites; Processing; Reinforcement; A: thermoplastics; Advanced applications; Biodegradable material; Composite matrix materials; Green composites; Natural fiber reinforced; Petrochemical based polymers; Polylactic acid blend; Polylactic acid composite; Thermoplastic polymer; Polyesters